2020
DOI: 10.1001/jamainternmed.2020.3930
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Home Health Care Workers in New York City During the Coronavirus Disease 2019 Pandemic

Abstract: IMPORTANCE Home health care workers care for community-dwelling adults and play an important role in supporting patients with confirmed and suspected coronavirus disease 2019 ) who remain at home. These workers are mostly middle-aged women and racial/ethnic minorities who typically earn low wages. Despite being integral to patient care, these workers are often neglected by the medical community and society at large; thus, developing a health care system capable of addressing the COVID-19 crisis and future pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
223
2
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(247 citation statements)
references
References 22 publications
(37 reference statements)
14
223
2
5
Order By: Relevance
“…Additionally, aides are vulnerable to community SARS-CoV-2 exposure due to their experience of social and economic inequities that present infection risks, such as housing where distancing is impossible. 2,4 The findings in this survey are consistent with several recent studies. 4,12,13 A case series study also documented COVID-19 illness among clients in home care.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, aides are vulnerable to community SARS-CoV-2 exposure due to their experience of social and economic inequities that present infection risks, such as housing where distancing is impossible. 2,4 The findings in this survey are consistent with several recent studies. 4,12,13 A case series study also documented COVID-19 illness among clients in home care.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the COVID-19 patient care provided by HH&HC agencies, early pandemic healthcare guidance, PPE, and educational and training resources were focused mainly on hospitals and nursing homes. [2][3][4] As a result, HH&HC managers spent time adapting guidance issued for facility-based healthcare to home-based care settings. For example, because aides' work remotely in private homes, procedures for storing/donning/doffing/disposing PPE differ from hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…The 1 study interviewed 33 home care home health and personal care aides and home attendants in 24 different home health agencies in the 5 boroughs of New York City. 9 The study found these workers: were on the front lines of the COVID 19 pandemic but felt invisible; reported a higher risk for virus transmission; received varying amounts of supplies, information, and training; relied on non-agency sources for support; and were forced to make difficult tradeoffs in work and their personal lives.…”
Section: Literature Reviewmentioning
confidence: 99%
“… 4 In the context of the coronavirus disease 2019 (COVID-19) pandemic, caregivers have become even more important, providing essential care to individuals with comorbid conditions and disabilities in the home. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%